2020
DOI: 10.1136/jitc-2020-001622
|View full text |Cite|
|
Sign up to set email alerts
|

Safety of immune checkpoint inhibitor rechallenge after discontinuation for grade ≥2 immune-related adverse events in patients with cancer

Abstract: BackgroundSafety of rechallenge of immune checkpoint inhibitor (ICI) after grade ≥2 immune-related adverse events (irAEs) leading to ICI discontinuation remains unclear.MethodsAll adverse drug reactions involving at least one ICI reported up to December 31, 2019 were extracted from the French pharmacovigilance database. Patients were included if they experienced at least one grade ≥2 irAE resulting in ICI discontinuation, with subsequent ICI rechallenge. The primary outcome was the recurrence of at least one g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 25 publications
(29 reference statements)
2
50
2
1
Order By: Relevance
“…GI irAEs were more likely to recur; however, there was no correlation between the severity of initial and subsequent irAEs. 279…”
Section: Rechallengingmentioning
confidence: 99%
“…GI irAEs were more likely to recur; however, there was no correlation between the severity of initial and subsequent irAEs. 279…”
Section: Rechallengingmentioning
confidence: 99%
“…Among these recurrent irAEs, colitis showed significantly higher incidence than other irAEs (227). Nearly 20%-30% of patients would experience recurrent grade 3 CIC (195,233). In our analysis, 12.5% (4/32) of patients (36,43,50,54) were retreated with the same ICI therapy used before, one of which experienced the recurrence of grade 3 enterocolitis (54).…”
Section: Rechallenge and Recurrencementioning
confidence: 60%
“…Gobbini et al (231) demonstrated that NSCLC patients discontinuing for irAEs had more prolonged survival than those discontinuing for disease progression. After ICI rechallenge, the recurrence rate of irAEs varied from 37% to 78% (227,(232)(233)(234). Among these recurrent irAEs, colitis showed significantly higher incidence than other irAEs (227).…”
Section: Rechallenge and Recurrencementioning
confidence: 97%
“…And the variables associated with a higher recurrence rate of irAEs were anti-CTLA-4 regimen, age, colitis, hepatitis, and pneumonia, in order [ 68 ]. In addition, the duration from ICI discontinuation to rechallenge, and the severity of the initial irAEs did not predict whether irAEs would reappear after rechallenge of ICIs [ 69 ]. However, no relevant literature has been reported on whether discontinuation due to ICI-related GBS can rechallenge the same or different ICIs again.…”
Section: Discussionmentioning
confidence: 99%